Pengaruh Corporate Governance dan Financial Distress terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Manufaktur yang terhdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Nova Agnia Astika; Ardan Gani Asalam (UNIVED Press, 2023)
Tax aggressiveness refers to the company's efforts to reduce its tax burden through tax planning, both through legal (tax avoidance) and illegal (tax evasion) methods. This tax aggressiveness is one of the causes of delays in state tax receipts. Therefore, for the government this action can cause considerable losses, because taxation is one of the highest sources of national income. This study was conducted with the aim of knowing the effect of institutional ownership, managerial ownership, audit quality, and financial distress on tax aggressiveness using the effective tax rate (ETR) proxy. The population in this study are manufacturing companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique used in this study was purposive sampling and 24 companies were obtained with a five-year period so that the number of samples in this study was 120 samples. This study uses panel data analysis method using Eviews 12 software. The findings of this study show that institutional ownership, managerial ownership, and audit quality have no effect on tax aggressiveness, while financial distress has a negative effect on tax aggressiveness.